Selective and sensitive fluorescence imaging reveals microenvironment-dependent behavior of NO modulators in the endothelial system - Ying Dong; Xiao-Rong Li; Jia Li; Yi Zang; Xin Li (Elsevier, 2020)
Nitric oxide (NO) is a second messenger playing crucial roles in the signaling of a variety of cellular functions. Due to its pathophysiological significance, various NO modulators have been developed to explore NO pathways and some have been used as therapies. These modulators are often used directly to observe pharmacological effects in cell lines, but their actual effect on intracellular NO level is seldom analyzed. Herein, facilitated by a selective and sensitive fluorescence probe, we observed that some NO modulators displayed unexpected behaviors with both NO scavenger carboxy-PTIO and endothelial nitric oxide synthase (eNOS) inhibitor N(ω)-nitro-l-arginine methyl ester (l-NAME) failing to decrease intracellular free NO level in EA. hy926 cells while NO donor diethylamine-NONOate (DEA·NONOate) and eNOS activator calcimycin (A23187) failing to increase free NO level in human umbilical vein endothelial cell line (HUV-EC-C), although the reagents were confirmed to work normally in the primary human umbilical vein endothelial cells (primary HUVECs) and RAW 264.7 macrophage cells. Further research suggested that these unusual behaviors might be attributed to the cellular microenvironments including both the NO synthase (NOS) level and the endogenous glutathione (GSH) level. Genetically manipulating eNOS level in both cells restores the expected response, while decreasing GSH level restores the ability of DEA·NONOate to increase NO level in HUV-EC-C. These results reveal that the cellular microenvironment has a profound impact on pharmacological effect. Our study suggests GSH as a reservoir for NO in live cells and highlights the value of chemical probes as valuable tools to reveal microenvironment-dependent pharmacological effects.